Proteshtags.: Zur Herstellung von (Protest-)Ereignissen durch situationsbezogene Hashtags - Dang-Anh, Mark (Linguistik Online, 2025)
This article aims to show how events are constituted through the use of situation-related hashtags and how the constitution of events can be understood by analysing situation-related hashtags. The events described are essentially political protest events that take place in situations of street protest. In the context of protest events, hashtags are used on Social Media to mark individual postings as belonging to events. Similarly, event and situation-related hashtags are used to (co-)constitute events in the first place. The word formation of protest event hashtags (proteshtags for short) follows a specific pattern: in addition to the hash as hashtag operator, they are composed of a place name or a corresponding topos-referential acronym as well as a chrono-referential date in the form DDMM (days and months). Using a data set of Twitter posts sent between November 2019 and October 2020, it is shown a) which events were marked by protest event hashtags during this period and b) how these events were tweeted about.